Note—A Goals/Values Solution to Mandatory Retirement Age for Tenured Faculty: An Application of Situational Normativism - Shakun, Melvin F.; Sudit, Ephraim F. (Management Science, 1978)
The controversial issue of mandatory retirement at age 70 for tenured faculty as considered by Congress is discussed using a goals/values analysis. A solution is proposed which permits such faculty to remain on active tenured status between ages 65 and 70 on a half-time basis only.